2015
DOI: 10.1097/rlu.0000000000000958
|View full text |Cite
|
Sign up to set email alerts
|

Long-Lasting FDG Uptake in the Muscles After Strenuous Exercise

Abstract: FDG PET/CT imaging guidelines require avoiding exercise 24 hours before FDG administration. We report here a case of intense skeletal muscle FDG activity in a 15-year-old adolescent boy who had vigorous exercise 4 days before undertaking FDG PET/CT scan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…In the muscle hypertrophy literature, as well as in our own research, we found evidence that a hypertrophying skeletal muscle reprograms its metabolism in a similar manner to cancer cells. For example, growing muscles take up more glucose over several days after a bout of resistance exercise [ 17 , 18 ]. Furthermore, the muscle growth factor IGF-1 increases lactate dehydrogenase expression and glycolytic flux in hypertrophying C2C12 myotubes [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the muscle hypertrophy literature, as well as in our own research, we found evidence that a hypertrophying skeletal muscle reprograms its metabolism in a similar manner to cancer cells. For example, growing muscles take up more glucose over several days after a bout of resistance exercise [ 17 , 18 ]. Furthermore, the muscle growth factor IGF-1 increases lactate dehydrogenase expression and glycolytic flux in hypertrophying C2C12 myotubes [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Further history taking revealed that the patient had strenuous exercise 4 days before the scan. [ 6 ]…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the submental activity was interpreted as genioglossus muscle activity due to sucking on a pacifier. Elevated FDG activity in the major muscles due to exertion is well-described [6][7][8][9][10] and rarely causes diagnostic dilemma. However, focal genioglossus muscle activity due to sucking in toddlers was much less recognized.…”
mentioning
confidence: 99%